Предмет: Математика,
автор: MinYoongi0613
СРОЧНО, ПОМОГИТЕ ПОЖАЛУЙСТА!!!
x+(x-2)+(2,3*x)+(2+(2,3*x))=46,2
Упростите выражение, и решите его. Помогите пожалуйста!!
Ответы
Автор ответа:
1
х+х-2+2,3х+2+2,3х=46,2
2х+2,3х+2,3х=46,2
6,6х=46,2
х=46,2/6,6
х=7
2х+2,3х+2,3х=46,2
6,6х=46,2
х=46,2/6,6
х=7
MinYoongi0613:
спасибо!!
Похожие вопросы
Предмет: Литература,
автор: Софья85
Предмет: Алгебра,
автор: Lenka1402
Предмет: Математика,
автор: altana20013
Предмет: Математика,
автор: 066906900az
Предмет: Физика,
автор: samir1212